Монголын шатах ашигт малтмал, тэдгээрийг агуулсан тунамал савууд - Б., Эрдэнэцогт (Geological Issues, 2022)
During the last decade, significant geological studies on fossil fuels and sedimentary basins in Mongolia have been completed; e.g., more than 100 coal deposits were explored. This review includes recent advances in tectonic setting of sedimentary basins, depositional environments of fossil fuel hosting sedimentary rocks, and quality and resources of coal, oil shale and petroleum source rocks. It also covers the results of coking coal blending studies, oil shale pyrolysis and the outcome of the first evaluation of coal bed methane potential of Mongolia.